Effectiveness of Drug Allergy Management: A Meta-Analysis - Saputra Poedjijo, Yanuar Surya; Raveinal; Dwitya Elvira (HM Publisher, 2024)
Background: Drug allergies pose a significant challenge in clinical practice, impacting patient safety and treatment options. This meta-analysis aims to evaluate the effectiveness of various drug allergy management strategies, including desensitization, graded challenges, and alternative medications. Methods: A systematic search of electronic databases (PubMed, Embase, Cochrane Library) was conducted from 2018 to 2024. Randomized controlled trials (RCTs) and observational studies assessing drug allergy management interventions were included. The primary outcome was the successful administration of the culprit drug without allergic reactions. Secondary outcomes included adverse events and quality of life. Data were extracted and pooled using random-effects models. Results: A total of 32 studies (15 RCTs, 17 observational studies) encompassing 4,215 patients were included. Desensitization protocols demonstrated a high success rate (89%) in enabling the administration of culprit drugs. Graded challenges also showed promising results (75% success rate). The use of alternative medications was associated with a lower risk of allergic reactions but may compromise treatment efficacy in some cases. Conclusion: This meta-analysis highlights the effectiveness of drug allergy management strategies, particularly desensitization and graded challenges. These interventions offer promising avenues to overcome drug allergies and optimize patient care. Further research is needed to explore long-term outcomes and refine management protocols.